In-situ Detection Method for Microplastics in Water by Polarized Light Scattering - Liu, Tong; Yu, Shijun; Zhu, Xiaoshan; Liao, Ran; Zhuo, Zepeng; He, Yanping; Ma, Hui (Frontiers in Marine Science, 2021)
Microplastics (MPs) have become the widespread contaminants, which raises concerns on their ecological hazards. In-situ detection of MP in water bodies is essential for clear assessment of the ecological risks of MPs. The present study proposes a method based on polarized light scattering which measures the polarization parameters of the scattered light at 120° to detect MP in water. This method takes the advantage of in-situ measurement of the individual particles and the experimental setup in principle is used. By use of the measured polarization parameters equipped by machine learning, the standard polystyrene (PS) spheres, natural water sample, and lab-cultured microalgae are explicitly discriminated, and MP with different physical and chemical properties can be differentiated. It can also characterize the weathering of different MP and identify the specific type from multiple types of MP. This study explores the capability of the proposed method to detect the physical and chemical properties, weathering state and concentration of MP in water which promises the future application in water quality sensing and monitoring.